2014 IEEE International Conference on Communications Workshops (ICC) 2014
DOI: 10.1109/iccw.2014.6881292
|View full text |Cite
|
Sign up to set email alerts
|

Parallel distributed Neyman-Pearson detection with privacy constraints

Abstract: In this paper, the privacy problem of a parallel distributed detection system vulnerable to an eavesdropper is proposed and studied in the Neyman-Pearson formulation. The privacy leakage is evaluated by a metric related to the Neyman-Pearson criterion. We will show that it is sufficient to consider a deterministic likelihood-ratio test for the optimal detection strategy at the eavesdropped sensor. This fundamental insight helps to simplify the problem to find the optimal privacy-constrained distributed detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…It turns out that the sensor that is being intercepted manipulates its feedback so that the EFC gains practically no information about the true hypothesis, while the LFC still extracts some useful information. The same network scenario was studied assuming Neyman-Pearson detectors in [45], where security was modeled using a constraint placed on the EFC detection probability. Here, it was shown that the optimal local quantizer is a deterministic LRT, while the fusion rule may still be a randomization between two or more LRTs.…”
Section: ) Optimal Quantizationmentioning
confidence: 99%
“…It turns out that the sensor that is being intercepted manipulates its feedback so that the EFC gains practically no information about the true hypothesis, while the LFC still extracts some useful information. The same network scenario was studied assuming Neyman-Pearson detectors in [45], where security was modeled using a constraint placed on the EFC detection probability. Here, it was shown that the optimal local quantizer is a deterministic LRT, while the fusion rule may still be a randomization between two or more LRTs.…”
Section: ) Optimal Quantizationmentioning
confidence: 99%
“…Moreover, the crucial energy efficient issue was not discussed. In [26,27], the optimal local quantizer was examined through minimizing the detection cost at the AFC meanwhile satisfying the constraints to the EFC detection cost or error performance, but the energy consumption problem was not concerned, either. In addition, all of the above solutions were not evaluated over a practical wireless channel and the effect of the transmission channel on their security was not discussed.…”
Section: Related Workmentioning
confidence: 99%
“…For the practical resource constraints and the serious security issues in front of WSN, secure distributed detection schemes under energy constraints are necessary for the development of an efficient IoT. Various secure strategies for distributed detection have been proposed under different assumptions on the eavesdroppers and transmission channels [8,9,10,23,24,25,26,27,28,29]. However, these studies focused on either the local detection at sensors or the information transmission from sensors to the FC.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the problem of Byzantines in the distributed detection network gains more attention recently [19], [20]. In [21], we studied the privacy-constrained parallel distributed Neyman-Pearson detection problem where the detection performance and eavesdropping privacy risk are evaluated by the Neyman-Pearson detection-operational metrics. For an optimal privacy-constrained distributed Neyman-Pearson detection design, it is sufficient to consider deterministic LRTs for the remote decision makers while a randomized fusion strategy might be needed.…”
mentioning
confidence: 99%